(3bhGYO GdeSDhdjI GdJCOjHjI aj VhA CMcGe GdeMceI GdEOGQjI GdYdjG (B/s - (3GdHgj, SejQ jhSas ((3GdbGgQI(B: s (3OGQ GdcJH GdbGfhfjI(B, s, 2002)
(3GdLQjeI GdJCOjHjI dGJNVY dbGYOI dG LQjeI HOhf fU(B- (3GdEWGQ GdTQYj dMb GdTchi GdeSDhdjI GdETQGajI(B- (3VhGHW hLhO GdeSDhdjI CefGA GdeNGRf hCQHGH GdYgO(B- (3JUQaGJ GdYGed aj MjGJg GdNGUI ceUOQ ddPfH GdEOGQj(B- (3GdTQhW GdELQGFjI ddJMbjb(B- (3GdEJUGd HGdJMbjb jchf HfGA Ydi JbGQjQ fgGFjI hdjSJ eHOFjI(B- (3CYVGA GdEOGQGJ GdbGfhfjI GdTQhW GdehVhYjI ddJMbjb(B- (3GdWYf Ydi bQGQ GdLRGA ejYGO GdWYf hHOA SQjGfg(B- (3GdeMceI GdJCOjHjI GdeNJUI eMdjG hhXjajG(B- (3JbQjQ GdWYf(B- (3GdEWGQ GdTQYj ddbQGQGJ GdUGOQI Yf eLGdS GdJCOjH(B.s
Keywords: (3GdbGfhf GdEOGQjs; (3GdeSDhdjI GdJCOjHjIs